Optimizing the Use of the Dapodik Application in School Data Synchronization to Improve the Efficiency of Education Management - Nur Ali Yasin; Febby Eka Elsalina (Yayasan Insan Mulia Bima, 2025)
This study discusses the optimization of the data synchronization process in the Dapodik Application at SDN 2 Kalipuro as part of strengthening the governance of basic education data. The Ministry of Education, Culture, Research, and Technology continues to update the Dapodik system even though its implementation in educational units still faces a number of technical obstacles. The main problem at SDN 2 Kalipuro that occurred was the limited capacity of the available Wi-Fi network. Unstable internet connections and limited bandwidth caused the synchronization process to often be slow or fail, so operators were forced to synchronize at night when network traffic was lighter. This study uses a descriptive qualitative approach with observation and interview methods with operators and principals. The results of the study show that the active role of the principal in supporting operational techniques and the perseverance of school operators are key to overcoming these limitations. Strategies such as scheduling synchronization outside of working hours and internal data management have proven effective in maintaining smooth data reporting. This study recommends increasing network capacity and technical training for operators to support the accuracy and sustainability of education data collection.